Pre-exposure prophylaxis (PrEP) in Australia: are there challenges facing sexual health promotion?. (25th October 2021) - Dunn, Matthew; Barnett, Anthony; McKay, Fiona H
Abstract: Pre-exposure prophylaxis (PrEP) for HIV refers to the daily use of antiretroviral medications by HIV uninfected persons to block a potential HIV infection. There is evidence to show that as the use of PrEP increases, the use of other safer sex practices such as condoms decreases, which may lead to an increase in sexually transmitted infections (STIs). This study aimed to explore whether PrEP had caused any challenges for organizations undertaking sexual health promotion activities in Australia. In-depth, semi-structured interviews were conducted with 17 participants (15 males, 2 females) who were purposively sampled from a range of HIV advocacy and health promotion settings. These included publicly funded HIV/AIDS councils and organizations representing people living with HIV/AIDS. Guided by an exploratory, inductive approach, the interviews were analyzed using thematic analysis. Three themes were constructed from the data analysis. First, organizations in different jurisdictions came to support PrEP in different ways, and this influenced the way organizations engaged with PrEP and the messaging that they disseminated to their community. Second, organizations faced some barriers to promoting PrEP, with the most significant being overcoming decades of HIV prevention campaigns that focused on barrier methods only. Third, there were social benefits to PrEP, such as shifting the onus of preventing HIV transmission from HIV positive to HIV negative people. PrEP is a highly effective biomedical intervention to reduce HIV transmission, and future challenges include designing campaigns for those at risk for HIV transmission outside the MSM community.